Does Culture Matter or Firm? Demand for Female Labor in Three Indian Cities - Das, Maitreyi Bordia; Mehta, Soumya Kapoor; Zumbyte, Ieva; Sasmal, Sanjeev; Goyal, Sangeeta (World Bank, Washington, DC, 2019)
In discussing the inordinately low employment of Indian women in urban areas, several studies have argued that culture and attitudes have created a labor market that is inherently discriminatory. The unsaid corollary is that culture is slow and hard to change and so, women will stay out of the labor market until social change occurs. The empirical evidence on the role of culture is slim at best. This paper fills the void in the policy literature, as it assesses the relative role of culture, as signified by attitudes of employers, and firm characteristics in hiring women. The paper is based on a unique survey of 618 firms in three of the largest cities in the state of Madhya Pradesh (India)—Bhopal, Indore, and Gwalior. Using detailed descriptive, bivariate and multivariate analysis at the firm level, the hiring process, and attitudes toward male and female workers, the paper addresses the issue of culture and firm characteristics, while noting that the two are not necessarily in binary opposition. The results reinforce the conventional wisdom in some ways and are surprising in others. The most salient result is that employer attitudes matter much less for the chance that women will be hired, than do firm and location characteristics. This has significant policy implications, the most important of which is that female employment in urban India is amenable to policy intervention, and that it is not necessary to wait for culture to change.